Environmental enrichment interaction for laboratory beagle dogs used in research - Fernandes, Anna Julia Bessa; Campos, Fernanda da Silva Freitas; Oliveira, Gabriella Santos; Oliveira, Priscila Cardim; Borges, Debora Azevedo; Pedrosa, Ivan de Alamar; Scott, Fabio Barbour (Brazilian Journal of Veterinary Medicine, 2024)
Experimental animal facilities can have a negative impact on the well-being of animals owing to confinement. To mitigate this, environmental enrichment (EE) is implemented confinement. The purpose of EE is to enhance the complexity of an animal’s natural environment. The objective of this study was to identify the types of EE most enjoyed by dogs used in experimental research and housed in individual kennels. A total of six adult Beagle dogs, housed at the Laboratório de Quimioterapia Experimental em Parasitologia Veterinária (LQEPV) at the Universidade Federal Rural do Rio de Janeiro (UFRRJ) were included in the study. The EE tools used included Petball® toys, a grassy outdoor area, interaction with other dogs and with a team member, a “pool” made of plastic bottles, and dog’s wet food ice cream. A team member assessed the usage of these tools every 5 min for a 30-min period, six times per day, one day per week, over the course of eight weeks. The study revealed that the grass area was the tool most commonly used for physical enrichment, accounting for 58% of the occurrences (p < 0.05). Social and food enrichment were enjoyed in second and third place, with 23% and 19% of occurrences, respectively. that the study findings suggest that dogs housed in individual kennels enjoy engaging in their natural behaviors.